2010
DOI: 10.1029/2010gc003064
|View full text |Cite
|
Sign up to set email alerts
|

Origin of volcanic seamounts at the continental margin of California related to changes in plate margins

Abstract: [1] Volcanic samples collected with the Monterey Bay Aquarium Research Institute's ROV Tiburon from eight seamounts at the continental margin offshore central to southern California comprise a diverse suite of mainly alkalic basalt to trachyte but also include rare tholeiitic basalt and basanite. All samples experienced complex crystal fractionation probably near the crust/mantle boundary, based on the presence in some of mantle xenoliths. Incompatible trace elements, poorly correlated with isotopic compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 66 publications
1
21
0
Order By: Relevance
“…The samples analyzed for Sr isotopes were subjected to a harsh HCl‐leaching procedure to remove seawater alteration effects, and thus, alteration is also not a likely cause of the spread in Sr isotope values. Davis et al [2010] observed variable Sr isotope ratios from other southern California seamount lavas as well and thus the spread of 87 Sr/ 86 Sr values is most likely a source feature of Davidson seamount lavas. Both highly incompatible trace element and Sr, Nd and Pb isotope ratios are not affected by normal partial melting and fractional crystallization processes and thus these ratios suggest that both alkalic and transitional lavas came from a common, though moderately heterogeneous mantle source or sources.…”
Section: Discussion and Interpretationmentioning
confidence: 82%
See 1 more Smart Citation
“…The samples analyzed for Sr isotopes were subjected to a harsh HCl‐leaching procedure to remove seawater alteration effects, and thus, alteration is also not a likely cause of the spread in Sr isotope values. Davis et al [2010] observed variable Sr isotope ratios from other southern California seamount lavas as well and thus the spread of 87 Sr/ 86 Sr values is most likely a source feature of Davidson seamount lavas. Both highly incompatible trace element and Sr, Nd and Pb isotope ratios are not affected by normal partial melting and fractional crystallization processes and thus these ratios suggest that both alkalic and transitional lavas came from a common, though moderately heterogeneous mantle source or sources.…”
Section: Discussion and Interpretationmentioning
confidence: 82%
“…This combined tectonic and mantle‐melting process produces voluminous mid‐ocean ridge basalt (MORB) with a fairly uniform major element composition that is distinct from magmatism at subduction zones and intraplate hot spots. The majority of fossil spreading centers in the eastern Pacific (Figure 1) are occupied by volcanic ridges that were built after the cessation of seafloor spreading activities [e.g., Batiza et al , 1982; Batiza and Vanko , 1985; Lonsdale and Castillo , 1998; Davis et al , 1995, 2002; Clague et al , 2009; Davis et al , 2010]. The composition of these ridges is distinct from that of normal MORB.…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 12. [Ce/Yb] N -Ce plot of Davis et al (2010). Note that samples show varying degrees of partial melting and that only one (P920A) is a product of crystal fractionation.…”
Section: Resultsmentioning
confidence: 97%
“…Further out on the Pacific plate, distinctive magmatic and isotope lineages develop on oceanic islands that are derived from low-SiO 2 mafic parents. Magma from depths of 100 km or more produces rocks with even lower SiO 2 (62)(63)(64). With great distance and lithospheric age, basalts from oceanic islands are even more enriched and diverse (48,49), indications of still lower fractions of partial melting.…”
Section: Geochemical Reservoirsmentioning
confidence: 99%